A contribution to demand analysis - Pearce, Ivor F. (Oxford : Clarendon Press, 1964)
Paradoxically the theory of demand, as it is commonly presented, is both too general and not general enough.
Includes index.
II 17/01/2019
Loans
Keywords: Supply and demand; Consumption (Economics)